Concevoir une médiation par le paysage comme outil d’appropriation des enjeux alimentaires par les habitants - Flora Rich; Yves Petit-Berghem (Développement Durable et Territoires)
It is now given that home gardens contribute to food systems. However, conditions of participation of the home gardeners in the development policies of sustainable food territories remain poorly conceptualized. Based on the case of Magny-en-Vexin (95), this article aims to define a methodolical approach for a landscape mediation approach likely to enrich the reflections in progress around the implementation of a Projet alimentaire territorial supported by the Parc naturel régional du Vexin français. By mobilising the results of a diachronic cartographic analysis and a field survey, this contribution shows that a better knowledge of gardening practices at the communal level can provide keys for an appropriation of the stakes of self-production and, more generally, of food by local actors, including the inhabitants.